1994
DOI: 10.1136/adc.70.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of enteral feeds.

Abstract: Enteral nutrition is increasingly used to provide nutritional support for children in hospital and at home. No suitable formula is available for preschool children, however, and until recently a modular feed has been prepared. The hypotheses were exmined that the use of a modular feed is associated with increased bacterial contamination, and that contamination is more common in the home than in hospital. Thirty five children receiving enteral nutrition initially in hospital and subsequently at home were alloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 13 publications
(12 reference statements)
0
39
0
6
Order By: Relevance
“…A administração de dieta eventualmente contaminada por diferentes microorganismos pode causar distúrbios gastrintestinais como náuseas, vômitos ou diarréias, sendo esta última, a complicação mais comum em pacientes que recebem NE 3 . Além disso, contaminações de origem microbiana em NE já foram documentadas, causando severas complicações infecciosas como septicemia, bacteremia e pneumonia 5 . Sendo assim, a utilização de NE deve seguir cuidados e procedimentos criteriosos, principalmente com o objetivo de controlar as possíveis fontes de contaminação das formulações.…”
Section: N T R O D U ç ã Ounclassified
See 1 more Smart Citation
“…A administração de dieta eventualmente contaminada por diferentes microorganismos pode causar distúrbios gastrintestinais como náuseas, vômitos ou diarréias, sendo esta última, a complicação mais comum em pacientes que recebem NE 3 . Além disso, contaminações de origem microbiana em NE já foram documentadas, causando severas complicações infecciosas como septicemia, bacteremia e pneumonia 5 . Sendo assim, a utilização de NE deve seguir cuidados e procedimentos criteriosos, principalmente com o objetivo de controlar as possíveis fontes de contaminação das formulações.…”
Section: N T R O D U ç ã Ounclassified
“…A contagem média de bactérias foi reduzida de 105 UFC/mL para <101 UFC/mL, após implantação desse sistema. Patchell et al 5 demonstraram que treinamento e implementação .…”
Section: R E S U L T a D O S E D I S C U S S ã Ounclassified
“…26 FEED SAFETY Microbiological contamination of enteral tube feeds can occur even with the use of commercial formulas. 29 Risk factors include the environment and manner in which the feed is prepared, poor attention to hygiene during handling, repeated topping up of the feed container and increasing feed-hanging times. 25 Commercially available 'ready to hang' closed enteral feeding systems are designed to limit handling procedures with the introduction of the giving set spike into the pack.…”
Section: Home-prepared Formulationsmentioning
confidence: 99%
“…In a previous study by Patchell et al (1994) it was found that 45% of feed samples were contaminated at the end of administration in feeding systems where feed was decanted in the hospital environment, and 29% of these contained 10 4 cfu ml -1 . Sixty-two per cent of feeds administered in the home were contaminated at the end of administration, with 45% containing 10 4 cfu ml -1 .…”
Section: Discussionmentioning
confidence: 97%
“…Although most commercially prepared feeds and feeding systems are now supplied sterile, several studies carried out on feeds intended for adult patients have demonstrated that bacteria can be introduced into the systems during the procedures involved in decanting feed into the nutrient container used during administration (White et al 1979, Anderton and Aidoo 1990, Weenk et al 1993. A study carried out by Schreiner et al (1979) on decanting feeds for neonates and one carried out by Patchell et al (1994) on feeds intended for infants receiving enteral nutrition in hospital or at home have also demonstrated bacteria gaining entry to systems via this route. Assembly and manipulation of feeding systems have also been shown as procedures which can introduce bacteria into the systems (Schroeder et al 1983, Crocher et al 1986, Anderton and Aidoo 1988, Beattie and Anderton 1998, 1999 However, in a follow-up to their earlier study, Patchell et al (1998) demonstrated that staff education and modification of the enteral feeding protocol reduced both the levels and incidence of bacterial contamination.…”
Section: Introductionmentioning
confidence: 97%